JURIDICAL ANALYSIS OF ERADICATION OF CRIMINAL ACTS OF TERRORISM IN INDONESIA - Yasmirah Mandasari Saragih; Mhd. Ihwanuddin Hasibuan; Sulaiman; Ricky Pratama Ginting; Fadillah Aditya Pratama (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Indonesia is a country of law as stated in article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Therefore, Indonesia as a country of law means that all arrangements in national and social life and the state are based on applicable laws with the aim of protecting and regulate every community's rights and obligations so as to create a safe, peaceful and peaceful life. One of the functions of the state is to protect every citizen from all threats of crime both from within and from outside. Terrorism is one of the crimes that often occurs and can threaten the life of the nation in Indonesia. The bomb blast at the Makasar Cathedral Church and the attack on the National Police Headquarters are examples of real cases of terrorist attacks in Indonesia. The purpose of this research is to find out and analyze the factors that cause terrorism and what efforts the government must make to prevent criminal acts of terrorism in Indonesia from being effective. The research method used in this research is a normative juridical approach, namely research based on library data in order to collect secondary data and tertiary data related to the problem formulation in this research. The research specification used is analytical descriptive, that is, it does not only describe problems, but also analyzes using an approach to legal norms relating to criminal acts of terrorism, in this case the researcher examines efforts to eradicate and prevent criminal acts of terrorism based on the law. Number 5 of 2018 concerning the eradication of criminal acts of terrorism and is linked to the opinions of experts, and describes it in the form of research using secondary and tertiary data using qualitative research. Terrorist acts that occur in Indonesia cannot be separated from the influencing factors that cause terrorism to develop, such as narrow understanding of religion, minimal understanding of Pancasila ideology and even psychological factors. Many efforts have been made by the government to prevent the occurrence of criminal acts of terrorism, such as the formation of a special anti-terrorism agency and efforts to secure areas that have the potential for terrorism to carry out its actions. However, there are still many acts/cases of terrorist crimes that occur in Indonesia, such as the bombing of the Cathedral Church House of Worship in Makasar and the attack on the National Police Headquarters, showing that efforts to prevent terrorism in Indonesia have not been effective. So further efforts are still needed that are more focused on involving every level of society to participate in fighting terrorism and also involving former terrorists as an effort to eradicate terrorism from its roots.